Persepsi Publik dan Upaya Pengelolaan Lingkungan Berkelanjutan terhadap Kualitas Air Sungai Bedadung, Jawa Timur - Hendra Andiananta Pradana; Elida Novita; Bambang Herry Purnomoc (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
Environmental quality management must consider both public perceptions and actual environmental conditions. This study presents an integrated approach combining community perceptions and pollution source mapping to enhance sustainable river water quality management. This study aims to identify the distribution of pollution sources and assess community perceptions of the Bedadung River’s water quality in Jember Regency. The research involved compiling a pollution source inventory, distributing questionnaires to respondents, mapping pollution sources, and conducting data analysis. Water quality parameters observed included Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Coliform (TC) for the period 2016–2019. Sampling was conducted at five monitoring stations located across three sub-districts: Patrang, Sumbersari, and Kaliwates. A total of 400 respondents participated in the study. The findings indicate that pollution sources in the Bedadung River consist of 81% domestic, 10% agricultural, and 9% industrial inputs. Additionally, the measured BOD, COD, and TC levels exceeded the Class I water quality standards specified in Indonesia’s river water regulations. Based on community perceptions and considering the distribution of pollution sources, 58% of respondents perceived the river as polluted, while 42% considered it to be in good condition. These results highlight the importance of integrating scientific monitoring, community perception improvement, and environmental health mapping to support sustainable water quality management in the Bedadung River.